A systematic review and meta-analysis on the role of varicosity treatment in the context of truncal vein ablation. (September 2015) - Lane, TRA; Onida, S; Gohel, MS; Franklin, IJ; Davies, AH
Background: With the advent of endovenous truncal ablation under local anaesthetic for the treatment of varicose veins, the fate of varicosed tributaries has become controversial, with centres offering different timings of treatment, if offered at all. This study aims to review the literature assessing delayed and simultaneous varicosity treatment during truncal ablation. Methods: Randomised trials and cohort studies concerning varicosity treatment timing were identified through a systematic literature search. Requirements for further treatment, quality of life and rate of venous thrombotic events were assessed for meta-analysis. Results: Four studies were identified assessing need for further varicosity procedure, with no significant difference seen between simultaneous or delayed treatment ( p = 0.339). Two studies assessed quality of life, with simultaneous treatment providing significantly improved outcomes at six weeks ( p = 0.029) but not at 12 weeks ( p = 0.283). Studies examining venous thrombotic events showed no difference in venous thromboembolism rate between simultaneous or delayed treatment approaches ( p = 0.078). Conclusion: The evidence base regarding timing of varicosity treatment is sparse; however, it does show that simultaneous treatment of varicosities leads to early gains in quality of life, with a non-significant trend for fewer further procedures but more venous thrombotic events.